Waterborne Isolates of Campylobacter jejuni Are Able to Develop Aerotolerance, Survive Exposure to Low Temperature, and Interact With Acanthamoeba polyphaga - Shagieva, Ekaterina; Demnerova, Katerina; Michova, Hana (Frontiers in Microbiology, 2021)
Campylobacter jejuni is regarded as the leading cause of bacterial gastroenteritis around the world. Even though it is generally considered to be a sensitive microaerobic pathogen, it is able to survive in the environment outside of the intestinal tract of the host. This study aimed to assess the impact of selected environmental parameters on the survival of 14 C. jejuni isolates of different origins, including 12 water isolates. The isolates were tested for their antibiotic resistance, their ability to survive at low temperature (7°C), develop aerotolerance, and to interact with the potential protozoan host Acanthamoeba polyphaga. The antibiotic susceptibility was determined by standard disk diffusion according to EUCAST. Out of the 14 isolates, 8 were resistant to ciprofloxacin (CIP) and 5 to tetracycline (TET), while only one isolate was resistant to erythromycin (ERY). Five isolates were resistant to two different antibiotic classes. Tetracycline resistance was only observed in isolates isolated from wastewater and a clinical sample. Further, the isolates were tested for their survival at 7°C under both aerobic and microaerobic conditions using standard culture methods. The results showed that under microaerobic conditions, all isolates maintained their cultivability for 4 weeks without a significant decrease in the numbers of bacteria and variation between the isolates. However, significant differences were observed under aerobic conditions (AC). The incubation led to a decrease in the number of cultivable cells, with complete loss of cultivability after 2 weeks (one water isolate), 3 weeks (7 isolates), or 4 weeks of incubation (6 isolates). Further, all isolates were studied for their ability to develop aerotolerance by repetitive subcultivation under microaerobic and subsequently AC. Surprisingly, all isolates were able to adapt and grow under AC. As the last step, 5 isolates were selected to evaluate a potential protective effect provided by A. polyphaga. The cocultivation of isolates with the amoeba resulted in the survival of about 40% of cells treated with an otherwise lethal dose of gentamicin. In summary, C. jejuni is able to adapt and survive in a potentially detrimental environment for a prolonged period of time, which emphasizes the role of the environmental transmission route in the spread of campylobacteriosis.